2004
DOI: 10.1021/ja049408c
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Sorption in Functionalized Metal−Organic Frameworks

Abstract: Five porous metal-organic frameworks based on linking zinc oxide clusters with benzene-1,4-dicarboxylate, naphthalene-2,6-dicarboxylate, 4,5,9,10-tetrahydropyrene-2,7-dicarboxylate, 2,3,5,6-tetramethylbenzene-1,4-dicarboxylate, or benzene-1,3,5-tris(4-benzoate) were synthesized in gram-scale quantities to measure their hydrogen uptake properties. Hydrogen adsorption isotherms measured at 77 K show a distinct dependence of uptake on the nature of the link. At 1 atm, the materials sorb between 4.2 and 9.3 molecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

47
773
4
15

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 1,305 publications
(839 citation statements)
references
References 13 publications
47
773
4
15
Order By: Relevance
“…Reaction of the ethylene ketal of 2-bromopropiophenone (6) to 2-bromopropiophenone (7), 2-bromoethyl 2-phenylpropanoate (8), 2-chloroethyl 2-phenylpropanoate (9) and 5-methyl-6-phenyl-2,3-dihydro-1,4-dioxin (10). X = Br (8) or Cl (9). Table 8.…”
Section: Is Clearly the Major Product In Reactions With [Cu 3 A C H Tmentioning
confidence: 99%
See 1 more Smart Citation
“…Reaction of the ethylene ketal of 2-bromopropiophenone (6) to 2-bromopropiophenone (7), 2-bromoethyl 2-phenylpropanoate (8), 2-chloroethyl 2-phenylpropanoate (9) and 5-methyl-6-phenyl-2,3-dihydro-1,4-dioxin (10). X = Br (8) or Cl (9). Table 8.…”
Section: Is Clearly the Major Product In Reactions With [Cu 3 A C H Tmentioning
confidence: 99%
“…[1][2][3][4] In literature, the term MOF covers a wide assembly of hybrid compounds. [4,5] Because of the exceptionally high pore volume and surface area of MOFs, many research efforts have been spent to their application in the sorption of light gases, either as such [6][7][8][9][10] or after modification with, for example, Ba 2 + . [11] As porous materials, MOFs may also find applications in catalysis.…”
Section: Introductionmentioning
confidence: 99%
“…MOFs have advantages such as tunable porosity, chemical stability, ultrahigh specific surface area, and ability to tune the surface chemistry. These features have enabled MOFs to find applications in diverse research fields including heterogeneous catalysis,9 gas storage,10 separation,11 capture,12 and chemical sensing 13. The electrochemical properties of MOFs have recently received significant attention in the chemical literatures 14.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 23 shows the structure of different IRMOFs (having the same underlying topology) that are constructed by linking ZnO clusters with linear carboxylates. MOF-177 is formed by linking the same clusters with a trigonal carboxylate [136]. Table 8 lists the types of MOFs reported to date, along with their specific surface area and hydrogen capacity.…”
Section: Metal Organic Frameworkmentioning
confidence: 99%
“…Rowsell et al [136] reported hydrogen uptake measurements on five different MOF materials and found that IRMOF-11 showed largest hydrogen uptake (1.62 wt.%) at 77 K and 1.01 bar. Figure 25 shows results of a detailed investigation of hydrogen adsorption properties in seven different MOFs conducted by Wong-Foy et al [149].…”
Section: Metal Organic Frameworkmentioning
confidence: 99%